Microbiome-Assisted Crop Production Improves Nutrient Cycling and Reduces Fertilizer Dependency - Abhijit Debnath; Bashir A Alie; Chakpram Birendrajit; Imtilemla (Public Health, 2026)
The increasing concern over soil degradation and environmental impacts associated with excessive use of chemical fertilizers has led to growing interest in biologically driven nutrient management approaches. In this context, a field experiment was conducted during the Kharif season at the Agriculture Research Farm, Salema, Dhalai, Tripura, to evaluate the role of microbiome-assisted crop production in paddy cultivation. The study was carried out using a Randomized Block Design with ten treatments involving different combinations of recommended fertilizer doses and microbial inoculants, including Azotobacter, phosphate-solubilizing bacteria (PSB), and arbuscular mycorrhizal fungi (AMF). The results revealed that the integration of microbial consortia with reduced fertilizer levels significantly improved soil organic carbon, available nitrogen, phosphorus, and potassium compared to control treatments. The treatment receiving 75% recommended fertilizer dose along with microbial consortium recorded the highest grain yield (5.3 t ha⁻¹), while 50% fertilizer combined with consortium produced comparable yield (5.1 t ha⁻¹), indicating substantial scope for reducing chemical fertilizer inputs. Enhanced microbial biomass carbon, dehydrogenase activity, and soil respiration further confirmed improved soil biological activity and nutrient cycling. The findings suggest that microbiome-assisted nutrient management can effectively sustain crop productivity while reducing fertilizer dependency and improving soil health. This approach offers a promising pathway for sustainable and environmentally sound agricultural practices, particularly in regions with fragile soil ecosystems.